Final answer:
To convert the equation y-6=4(x+3) into slope-intercept form, distribute the 4 to both terms inside the parentheses, then isolate y by moving -6 to the opposite side of the equation.
Step-by-step explanation:
To convert the equation y - 6 = 4(x + 3) into slope-intercept form, we need to isolate y on one side of the equation. First, distribute the 4 to both terms inside the parentheses: y - 6 = 4x + 12. Next, move the constant term -6 to the opposite side of the equation by adding 6 to both sides: y = 4x + 18. The equation y = 4x + 18 is the slope-intercept form, where the slope is 4 and the y-intercept is 18.
Learn more about Slope-intercept form